Formation and growth dynamics of domains under phase transitions in an external field - Stefanovich, L. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The formation and the growth dynamics of 180° -domains in ferroelectrics in external field are investigated with the use of the statistical approach within the Ginzburg-Landau model. It is shown that despite the polarizing role of an external field the formation of an intermediate polydomain structure is found to be more preferable than immediate transfer to the monodomain ordering state.